Development of Decellularized Fish Skin Scaffold Decorated with Biosynthesized Silver Nanoparticles for Accelerated Burn Wound Healing - Surya Prasad Adhikari; Astha Paudel; Anisha Sharma; Baruna Thapa; Neha Khanal; Nisha Shastri; Sourav Rai; Rameshwar Adhikari (International Journal of Biomaterials)
In this study, decellularized fish skin (DFS) scaffold decorated with silver nanoparticles was prepared for accelerating burn wound healing. The silver nanoparticles (AgNPs) synthesized by the green and facile method using Aloe vera leaf at different incubating times were characterized by using X-ray Diffraction (XRD), Fourier Transform Infrared (FT-IR) Spectroscopy, and Ultraviolet-Visible Spectroscopy (UV-Vis spectroscopy). The different characterizations confirmed that the sizes of AgNPs prepared by incubating for 6 hours and 12 hours were 29.1 nm and 35.2 nm, respectively. After that, the different concentrations of the smallest AgNPs were used to dope the DFS scaffold to determine the cell viability. Additionally, an agar well diffusion method was used to screen for antimicrobial activity. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were used to correlate the concentration of AgNPs with its bactericidal effect which was seen from 50 μg/ml. Then, the toxicity with human cells was investigated using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay with no significant cell viability from the concentration of 50 μg/ml to 200 μg/ml compared to the cocultured and commercial treatments.